Analisis Pengaruh Elektrifikasi Pelanggan Industri, Rumah Tangga dan Sosial Terhadap Perkembangan Ekonomi Sektor Industri Mikro, Kecil dan Menengah di Kabupaten Mimika - Timotius Irto Ta’dungan; Yundy Hafizrianda (Universitas Cenderawasih, 2025)
This study aims to analyze the partial and simultaneous effects of electrification of industrial customers, household customers, and social customers on the economic development of the Micro, Small, and Medium Enterprises (MSMEs) sector in Mimika Regency. The method used in this research is an associative method with a quantitative approach using multiple linear regression analysis. The data used are secondary time series data over an eleven-year period sourced from the Central Statistics Agency of Mimika Regency and PT PLN UP3 Timika. Prior to regression analysis, classical assumption tests were conducted, including normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. Hypothesis testing was performed partially using the t-test and simultaneously using the F-test. The results showed that the regression model met all classical assumption tests, thus declared valid for further analysis. Partially, electrification of industrial customers had no significant effect on the GRDP growth of the MSME sector, while electrification of household customers and social customers had a significant effect. Simultaneously, all three electrification variables together had a significant effect on the GRDP growth of the MSME sector. The three types of electrification together were able to explain most of the variation in MSME GRDP. Based on these findings, it is concluded that household and social electrification are important factors in driving MSME growth in Mimika Regency, while industrial electrification has not yet provided a meaningful impact. As practical recommendations, the Mimika Regency Government and PT PLN are advised to prioritize the expansion of electricity networks to underserved areas, especially for household customers and social facilities such as schools and community health centers. Furthermore, it is necessary to encourage linkages between the large industrial sector and local MSMEs through partnership programs and local supply chains, as well as to provide affordable electricity programs for micro and small enterprises. Keywords: Customer Electrification, MSME Development, Multiple Linear Regression